Approximate algorithm for median query based on WSN - LIU Cai-ping1; MAO Jian-xu2; LI Ren-fa1; FU Bin1 (Tongxin xuebao)
An approximate algorithm for median query（AAMQ） based on WSN was proposed.In AAMQ,each node could estimate the value of the distinct number,and created a subsequence samples which get K percent of the most com-monly used values in its own observed values,and then broadcasted its subsequence to the parents.Finally,these samples were combined to a single sample in the root node which its data structure was far smaller than the size of the whole data set.The approximate value for median query could be introduced from the sample quickly.Experimental results show that the proposed algorithm can greatly reduce the communication,has the advantages of low error range,and is able to significantly prolong system life.